Análise da influência do tamanho da partícula na flotação da apatita em coluna - Santana, Ricardo Corrêa de (2007)
The phosphate industry moves in the world, billion of dollars. In Brazil, about 80% of the natural deposit of phosphate is from igneous source, with low grade of P2O5. The economical exploited of these deposits leads to losses of mineral values, demanding like this, more and more, improviments in the concentration process, in order to obtain a better use of the phosphorus sources. Among the major developments attained in the search to satisfy the strict market specifications, column flotation proved to be a proper technique for processing low grade ores, presenting a high liberation degree only at fine size ranges. Particle size is an important parameter on flotation process performance. Most of the observed results show, that for a given flotation system, there is an optimum flotation size range. Fine and coarse particles can lead difficulties in the recovery and/or grade of mineral values. Besides, in a conventional flotation machine there is an enormous difficulty of finding appropriate conditions for obtaining satisfactory recovery and grade in different particle size ranges. In such case, the aim of this work is to study the influence of the particle size on apatite flotation in column. For in such a way, multi-factor experimental designs was carried through, for all size fractions studied. Collector and depressant dosages was the variables analyzed. Ahead of the obtained results, it was made an analysis overall statistics and a canonical analysis in order to optimize the operational conditions. In accordance with the main experimental results, it was possible to find favorable conditions for recoverey and grade of P2O5 in the concentrate for different fractions. Reagents and particle size conditions were determined for better individually results of grade, recovery and selectivity as well as those conditions that lead to recovery values desired and apatite content above of 60 and 33 %, respectively. Particle size range from 37 to 105 µm attained of simultaneous way to satisfactory resulted of the answers apatite grade and recovery. For the analysis of the response surfaces it was observed that the conditions that increase the recovery are, high collector levels and low values for depressant dosage and particle size. For the canonical analysis, it was verified for the P2O5 grade that the conditions that maximize this answer are dosage of collector of 50 g/t, dosage of depressant of 220 g/t and average particle size equal to 269 µm.